Pendidikan Tanpa Konflik: Strategi Dikbud NTB dalam Menciptakan Keharmonisan - Supriadi; Suprapto; Abdul Malik (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to explore and analyze the strategies implemented by the West Nusa Tenggara (NTB) Department of Education and Culture (Dikbud) in creating education that is free from conflict and harmony. Using a descriptive qualitative methodology with a case study approach, this research found that increased communication between stakeholders, character education, and mediation as the main approaches in conflict resolution have succeeded in creating a conducive learning environment. Apart from that, the use of local wisdom and application of the principles of social justice and inclusiveness are important factors in reducing educational disparities. The research results show that these strategies not only increase harmonious relationships between educators, students, parents and the community, but also contribute to the development of student character. This research recommends strengthening mediation programs, more active community involvement, and inclusive education policies to ensure the continuation of peaceful education in NTB.